Application of organic lithium salt and method for repairing cathode material of lithium ion battery by directional reduction
Patent Information
- Application Number
- CN202310992956.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-08
AI Technical Summary
如公开号为CN106976852A中公开了一种废旧电池中磷酸铁锂材料的绿色修复再生技术,其在拆解得到磷酸铁锂粉末之后,通过加入锂源、铁源、磷源来调控LI、Fe、P的元素比例,再加入合适碳源,球磨之后高温烧结得到新的磷酸铁锂材料,再次过程中辅料的引入会造成新的杂质引入,对于磷酸铁锂的纯度造成干扰
[0034]本发明提供了一种有机锂盐在锂离子电池正极材料修复中的应用,所述有机锂盐由式(I)所示化合物与碱性锂盐形成。与现有技术相比,本发明提供的有机锂盐具有还原性质,对于锂离子电池正极材料尤其是磷酸铁锂正极材料在充放电过程中产生的反位缺陷具有很好的修复作用,且无杂质离子引入,产品纯度高,并于此同时,高温环境有机相碳化对于正极材料的有机相包覆效果可以改善其电化学性能,精简工艺流程,降低成本。
Smart Images

Figure CN117175032B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, and particularly relates to the application of organic lithium salts and a method for targeted reduction and repair of lithium-ion battery cathode materials. Background Technology
[0002] The main methods for recycling cathode materials from retired lithium iron phosphate batteries are solid-phase remediation and wet regeneration.
[0003] Wet regeneration involves directly dissolving lithium iron phosphate (LFP) in a strong acid solvent, followed by impurity removal, elemental adjustment, and precipitation to obtain a LFP precursor. Finally, the LFP is obtained through solid-state sintering. For example, Chinese patent CN106910889A discloses a method for regenerating positive electrode active material from spent LFP batteries. This method first disassembles the battery to obtain LFP powder, then uses strong acid leaching, iron impurity removal, and elemental adjustment to obtain the LFP precursor, and finally sinters the resulting LFP powder to obtain new LFP powder. While wet regeneration of LFP materials results in high purity and good repair performance, the complex and lengthy process inevitably leaves some elements in the reaction solution, affecting the recycling efficiency. Furthermore, wet leaching of LFP involves significant acid and alkali consumption, increasing production costs. In contrast, the solid-state remediation method has a shorter process flow and higher recycling efficiency, making it more suitable for LFP remediation and recycling.
[0004] Solid-state remediation generally employs high-temperature sintering to repair lattice defects in lithium iron phosphate (LFP) after charging and discharging, and to replenish missing lithium by adding lithium replenishing agents. For example, CN106976852A discloses a green remediation and regeneration technology for LFP materials in waste batteries. After disassembling to obtain LFP powder, the elemental ratios of Li, Fe, and P are adjusted by adding lithium, iron, and phosphorus sources, followed by the addition of a suitable carbon source. After ball milling, high-temperature sintering yields new LFP material. However, the introduction of auxiliary materials during this process introduces new impurities, interfering with the purity of the LFP. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide an application of organic lithium salt and a method for targeted reduction and repair of lithium-ion battery cathode materials. The organic lithium salt has reducing properties and has a good repair effect on the antisite defects generated in lithium-ion cathode materials during charging and discharging.
[0006] This invention provides an application of an organic lithium salt in the repair of cathode materials for lithium-ion batteries, wherein the organic lithium salt is formed by the compound shown in formula (I) and an alkaline lithium salt;
[0007]
[0008] Wherein, R1 is OH or COOH;
[0009] R2 is H or a C1-C5 alkyl group.
[0010] Preferably, the compound of formula (I) is selected from one or more of phenol, benzoic acid, p-phenylethylphenol, 2-ethylphenol and 3-ethylphenol;
[0011] The alkaline lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, and lithium bicarbonate;
[0012] The cathode material of the lithium-ion battery is lithium iron phosphate cathode material.
[0013] Preferably, the organolithium salt is prepared according to the following steps:
[0014] S) The compound shown in formula (I) is mixed with an aqueous solution of an alkaline lithium salt in an organic solvent, stirred and allowed to stand, the lower layer solution is separated, and the solvent is removed to obtain the organic lithium salt.
[0015] Preferably, step S) specifically comprises:
[0016] S1) Mix the compound shown in formula (I) with an organic solvent to obtain an organic solution of the compound shown in formula (I);
[0017] Alkaline lithium salt is mixed with water to obtain an aqueous solution of alkaline lithium salt;
[0018] S2) The organic solution of the compound shown in formula (I) is mixed with an alkaline lithium salt aqueous solution, stirred and reacted, then allowed to stand, the lower layer solution is separated, and the solvent is removed to obtain the organic lithium salt.
[0019] The mass concentration of the compound represented by formula (I) in the organic solution is 10% to 50%.
[0020] The concentration of alkaline lithium salt in the alkaline lithium salt aqueous solution is 0.1–2 mol / L.
[0021] Preferably, the organic solvent is selected from one or more of ethanol, methanol, ethylene glycol and diethyl ether; the stirring reaction time is 0.5 to 3 hours; and the standing time is 0.5 to 2 hours.
[0022] This invention also provides a method for targeted reduction and repair of lithium-ion battery cathode materials, comprising the following steps:
[0023] A1) Mix the organic lithium salt with the positive electrode material of the lithium-ion battery to be repaired to obtain a mixed material;
[0024] A2) The mixed material is sintered in a protective atmosphere to obtain the repaired lithium-ion battery cathode material.
[0025] Preferably, in step A1), the organic lithium salt and the positive electrode material of the lithium-ion battery to be repaired are mixed in a molar ratio of Li, Fe and P of (1-1.2):1:1.
[0026] Preferably, the mixing method in step A1) is ball milling; the ball-to-material ratio in the ball milling is 1:(5-15); the rotation speed of the ball milling is 300-500 r / min; and the ball milling time is 0.5-8 h.
[0027] Preferably, step A2) specifically comprises:
[0028] The mixed material is first subjected to low-temperature pretreatment in a protective atmosphere, and then solid-state sintering is performed to obtain the repaired lithium-ion battery cathode material.
[0029] The heating rate of the low-temperature pretreatment is 1–10 °C / min; the temperature of the low-temperature pretreatment is 100 °C–400 °C; and the holding time of the low-temperature pretreatment is 0–8 h.
[0030] The heating rate of the solid-state sintering is 1-10℃ / min; the solid-state sintering temperature is 400℃-1000℃; and the holding time of the solid-state sintering is 0-12h.
[0031] Preferably, the flow rate of the protective atmosphere is 0.1–3 L / min; the protective atmosphere is selected from one or more of hydrogen, argon, and nitrogen.
[0032] The heating rate of the low-temperature pretreatment is 3-6℃ / min; the temperature of the low-temperature pretreatment is 350℃-390℃; and the holding time of the low-temperature pretreatment is 1-3h.
[0033] The heating rate of the solid-state sintering is 3-6℃ / min; the solid-state sintering temperature is 600℃-700℃; and the holding time of the solid-state sintering is 6-10h.
[0034] This invention provides an application of an organic lithium salt in the repair of lithium-ion battery cathode materials. The organic lithium salt is formed by the compound shown in formula (I) and an alkaline lithium salt. Compared with existing technologies, the organic lithium salt provided by this invention has reducing properties, effectively repairing anti-site defects generated in lithium-ion battery cathode materials, especially lithium iron phosphate cathode materials, during charge and discharge processes. Furthermore, it introduces no impurity ions, resulting in high product purity. Simultaneously, the high-temperature organic phase carbonization improves the electrochemical performance of the cathode material through organic phase coating, simplifying the process and reducing costs.
[0035] Experimental results show that the solid-phase repair method provided by this invention has a good repair effect on retired lithium iron phosphate cathode materials. The battery capacity of the repaired lithium iron phosphate product can reach 150mAh / g at 0.2C, and the capacity retention rate can reach 94.12% after 200 charge-discharge cycles. Attached Figure Description
[0036] Figure 1 This is a flowchart illustrating the method for directional reduction and repair of lithium-ion battery cathode materials provided by the present invention. Detailed Implementation
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0038] This invention provides an application of an organic lithium salt in the repair of cathode materials for lithium-ion batteries, wherein the organic lithium salt is formed by the compound shown in formula (I) and an alkaline lithium salt;
[0039]
[0040] Wherein, R1 is OH or COOH;
[0041] R2 is an alkyl group consisting of H or C1 to C5, preferably an alkyl group consisting of H or C1 to C4, more preferably an alkyl group consisting of H or C1 to C3, and even more preferably an alkyl group consisting of H, methyl, or ethyl.
[0042] In this invention, the position of R2 can be adjacent, intermediate, or opposite to R1.
[0043] According to the present invention, most preferably, the compound of formula (I) is one or more of phenol, benzoic acid, p-phenylethylphenol, 2-ethylphenol and 3-ethylphenol.
[0044] According to the present invention, the alkaline lithium salt includes, but is not limited to, one or more of lithium hydroxide, lithium carbonate, and lithium bicarbonate.
[0045] According to the present invention, the organolithium salt is prepared by the following steps: S) The compound shown in formula (I) is mixed with an aqueous solution of alkaline lithium salt in an organic solvent, stirred and reacted, then allowed to stand, the lower layer solution is separated, and the solvent is removed to obtain the organolithium salt. The molar ratio of the compound shown in formula (I) to elemental lithium in the alkaline lithium salt is preferably (1-1.2):1, more preferably (1.1-1.2):1; the organic solvent is preferably one or more of ethanol, methanol, ethylene glycol and diethyl ether; the stirring reaction time is preferably 0.5-3h, more preferably 0.5-2h, even more preferably 0.5-1h, and most preferably 45min; the standing time is preferably 0.5-2h, more preferably 0.5-1.5h, even more preferably 0.8-1.2h, and most preferably 1h; after standing, the solution separates into layers, the lower layer solution is separated, and the solvent is removed; the method for removing the solvent is any method known to those skilled in the art and is not particularly limited. In the present invention, the solvent is preferably removed by evaporation to obtain crystals, which are the organolithium salt. In this invention, the preparation step is preferably as follows: S1) Mixing the compound shown in formula (I) with an organic solvent to obtain an organic solution of the compound shown in formula (I); mixing the alkaline lithium salt with water to obtain an aqueous solution of the alkaline lithium salt; S2) Mixing the organic solution of the compound shown in formula (I) with the aqueous solution of the alkaline lithium salt, stirring and reacting, allowing to stand, separating the lower layer solution, removing the solvent, and obtaining an organic lithium salt; the mass concentration of the compound shown in formula (I) in the organic solution is preferably 10% to 50%, more preferably 20% to 40%, even more preferably 25% to 35%, and most preferably 30%; the concentration of the alkaline lithium salt in the aqueous solution of the alkaline lithium salt is preferably 0.1 to 2 mol / L, more preferably 0.3 to 1.5 mol / L, and even more preferably 0.5 to 1 mol / L.
[0046] Taking phenol as the compound shown in formula (I) and lithium hydroxide as the basic lithium salt as an example, the reaction formula of the organolithium salt is as follows:
[0047]
[0048] According to the present invention, the preferred cathode material for the lithium-ion battery is lithium iron phosphate cathode material.
[0049] The organic lithium salt provided by this invention has reducing properties and can effectively repair the antisite defects generated in lithium-ion battery cathode materials, especially lithium iron phosphate cathode materials, during charging and discharging. It also introduces no impurity ions, resulting in high product purity. At the same time, the organic phase carbonization in a high-temperature environment can improve the electrochemical performance of the cathode material by enhancing its organic phase coating effect, simplifying the process, and reducing costs.
[0050] The present invention also provides a method for targeted reduction and repair of lithium-ion battery cathode materials, comprising the following steps: A1) mixing an organic lithium salt with the lithium-ion battery cathode material to be repaired to obtain a mixed material; A2) performing solid-state sintering of the mixed material in a protective atmosphere to obtain the repaired lithium-ion battery cathode material.
[0051] This invention uses organic lithium salts as lithium replenishing agents in the solid-phase repair of cathode materials in retired lithium-ion batteries. The high reducing power of the benzene rings in these salts can repair anti-site defects in lithium iron phosphate, and no additional lithium salt is needed during subsequent calcination, allowing for better modification of the lithium iron phosphate. The reducing power of the benzene rings can also remove Fe from the retired batteries. 3+ Reduced to Fe 2+ This process lowers the diffusion barrier for Fe to migrate to its original position, thus returning it to its original location. This effectively reduces the diffusion barrier for lithium in the lithium replenishment agent to enter the lithium iron phosphate material. Furthermore, organic lithium compounds have small molecular weights, are easy to synthesize, have low costs, and are less toxic (the larger the molecular weight of the organic compound, the more difficult the synthesis, and the lower the purity and toxicity). Moreover, this remediation method does not consume acid or alkali, has a simple process flow, low production costs, and a high recovery rate of retired lithium iron phosphate throughout the process. It can turn retired lithium iron phosphate batteries into valuable resources, avoiding the environmental harm caused by waste batteries, and is environmentally friendly.
[0052] In this invention, there are no special restrictions on the source of any raw materials; they can be commercially available.
[0053] An organic lithium salt is mixed with the cathode material of a lithium-ion battery to be repaired to obtain a mixed material; the cathode material of the lithium-ion battery to be repaired is preferably a lithium iron phosphate cathode material to be repaired; the organic lithium salt and the cathode material of the lithium-ion battery to be repaired are preferably mixed in a molar ratio of Li, Fe and P of (1-1.2):1:1, more preferably (1.01-1.2):1:1; in the embodiments provided by the present invention, the organic lithium salt and the cathode material of the lithium-ion battery to be repaired are preferably mixed in a molar ratio of Li, Fe and P of 1.01:1:1, 1.1:1:1, 1.05:1:1, or 1:1. The mixture is prepared in a ratio of 1:1.2:1:1 or 1.02:1:1; the mixing method is any method known to those skilled in the art and is not particularly limited. In this invention, ball milling is preferred; the ball-to-material ratio of the ball milling is preferably 1:(5-15), more preferably 1:(8-12), and even more preferably 1:10; the ball milling speed is preferably 300-500 r / min, more preferably 300-400 r / min, and even more preferably 350 r / min; the ball milling time is preferably 0.5-8 h, more preferably 1-5 h, even more preferably 1-3 h, even more preferably 1.5-2.5 h, and most preferably 2 h.
[0054] The mixed material is solid-state sintered in a protective atmosphere to obtain a repaired lithium-ion battery cathode material. In this invention, this step specifically involves: pre-treating the mixed material at low temperature in a protective atmosphere, followed by solid-state sintering to obtain the repaired lithium-ion battery cathode material. The protective atmosphere is preferably one or more of hydrogen, argon, and nitrogen, more preferably one or more of hydrogen, an argon-hydrogen mixture, and nitrogen. The flow rate of the protective atmosphere is preferably 0.1–3 L / min, more preferably 0.1–2 L / min, and even more preferably 1–2 L / min. The heating rate of the low-temperature pretreatment is preferably 1–10 °C / min, more preferably 2–8 °C / min, even more preferably 3–6 °C / min, and most preferably 5 °C / min. The temperature of the low-temperature pretreatment is preferably 100 °C–400 °C, more preferably 20 °C. The temperature range is 0℃~400℃, more preferably 300℃~400℃, even more preferably 350℃~390℃, and most preferably 375℃; the holding time for the low-temperature pretreatment is preferably 0~8h, more preferably 1~5h, even more preferably 1~3h, and most preferably 2h; the heating rate for the solid-state sintering is preferably 1~10℃ / min, more preferably 2~8℃ / min, even more preferably 3~6℃ / min, and most preferably 5℃ / min; the solid-state sintering temperature is preferably 400℃~1000℃, more preferably 500℃~800℃, even more preferably 600℃~700℃, and most preferably 675℃; the holding time for the solid-state sintering is preferably 0~12h, more preferably 3~12h, even more preferably 6~10h, and most preferably 8h; after solid-state sintering, it is preferable to allow natural cooling to room temperature to obtain the repaired lithium-ion battery cathode material. The advantages of using multi-stage sintering are as follows: the first stage of low-temperature roasting pretreatment serves to directionally reduce and repair the defective structure of lithium iron phosphate (because excessively high temperatures will cause organic matter to decompose, so low-temperature roasting reduction is used); the purpose of the second stage of roasting reduction is to coat the surface of the reduced lithium iron phosphate cathode material with a layer of carbon structure, which helps to improve electrochemical performance.
[0055] Taking the organic lithium salt formed by phenol and lithium hydroxide, and the lithium iron phosphate cathode material of the lithium-ion battery as an example, the process of solid-state sintering repair of the lithium-ion battery cathode material is as follows:
[0056]
[0057] The present invention describes a novel lithium replenishment method for the direct repair and organic phase coating of lithium iron phosphate (LFP) cathode materials. The process involves mixing and ball milling retired LFP cathode materials with a novel lithium replenishment agent, followed by solid-state sintering of the mixture. This process restores the capacity of the repaired LFP cathode material from 100 mAh / h to 140–150 mA / g. The repaired cathode material exhibits a complete structure and excellent performance, making it suitable for assembling new LFP cathode batteries. The organic lithium salt used in this method allows for effective bonding between the LFP cathode material and lithium ions, subsequently improving lithium replenishment efficiency. The reducing properties of the benzene ring repair anti-site defects in the LFP cathode material without requiring expensive or toxic reducing agents, ensuring high safety. The organic phase coating repair effect of the organic lithium salt on the LFP cathode material effectively extends the battery's cycle life.
[0058] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, provides a method for the application of organic lithium salts and the targeted reduction and repair of lithium-ion battery cathode materials.
[0059] All reagents used in the following examples are commercially available. The performance testing methods for the repaired lithium iron phosphate cathode material in the examples and comparative examples are as follows: The electrode slurry was mixed with 80 wt% of the repaired and regenerated lithium iron phosphate cathode material, 10 wt% of polyvinylidene fluoride (PVDF) binder, 10 wt% of acetylene black, and an appropriate amount of N-methylpyrrolidone (NMP) as solvent. The mixed slurry was evenly spread on aluminum foil and dried at 120°C for 6 hours. The coated electrode sheet was cut and compressed into circular electrodes, with the active material mass loading controlled at 1.2–1.5 mg / cm³. -1 Left and right. Choose 1 mol L. -1 LiPF6 was used as the electrolyte in a solution of ethylene carbonate / diethyl carbonate = 50:50 (v / v). The prepared lithium iron phosphate electrode (positive electrode), lithium metal (negative electrode), and Celgard-2500 (separator) were then assembled into a coin cell. Constant current discharge / charge tests were performed on a LAND test system (CT3002A) between 2.5V and 4.3V.
[0060] See Figure 1 , Figure 1 This is a flowchart illustrating the method for directional reduction and repair of lithium-ion battery cathode materials provided by the present invention.
[0061] S1: Preparation of organolithium salts
[0062] In step S1, the mixed solvent is ethanol, the lithium salt is selected from lithium hydroxide, and the organic source is phenol. Phenol reagent is added to the ethanol reagent to form a phenol organic solvent (mass concentration 10-50%). The lithium hydroxide aqueous solution is 0.1-2 mol / L; for example, the phenol organic solvent mass concentration is 30%, the lithium hydroxide aqueous solution is 0.5 mol / L, and the lithium to phenol molar ratio is 1:1.2. The mixture of lithium hydroxide and phenol organic solvent is stirred continuously for 0.5-3 hours until the reaction is complete. After standing for 0.5-2 hours, the solution separates into layers. The lower layer of lithium phenol solution is separated using a separatory funnel to obtain a lithium phenol solution. The lithium phenol solution is then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0063] S2: Material mixing, mixing of lithium phenolate and lithium iron phosphate waste.
[0064] The elemental content in lithium iron phosphate was determined, and the elemental molar ratio was adjusted to Li:Fe:P = 1.0-1.2:1:1. Solid lithium phenolate and lithium iron phosphate were loaded into a ball mill jar with a ball-to-material ratio of 1:10. The ball milling speed was 300-500 r / min, and the milling time was 0.5-8 h. After the ball milling was completed, the mixed powder was placed in an atmosphere furnace in preparation for solid-phase repair.
[0065] S3: Solid-phase repair
[0066] The ball-milled material was placed in an atmosphere furnace, and a protective atmosphere (hydrogen, a hydrogen-argon mixture, nitrogen, etc.) was introduced. The temperature was increased from room temperature to 100–400°C at a rate of 5°C / min, and held for 0–4 hours. The temperature was then increased to 400–1000°C at a rate of 5°C / min, and held for 0–12 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was introduced throughout the entire solid-phase repair process.
[0067] Example 1
[0068] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution. The molar ratio of lithium to phenol was 1:1.2. The lithium hydroxide and phenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of phenol-lithium solution was separated using a separatory funnel to obtain a phenol-lithium solution. This solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0069] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and load solid lithium phenolate and lithium iron phosphate into a ball mill jar according to the element molar ratio: Li:Fe:P = 1.01:1:1, with a ball-to-material ratio of 1:10. The ball milling speed is 350r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace to prepare for solid phase repair.
[0070] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0071] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 150 mAh / g. After 200 cycles, the battery capacity retention rate was 94.12%.
[0072] Example 2
[0073] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution. The molar ratio of lithium to phenol was 1:1.2. The lithium hydroxide and phenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of phenol-lithium solution was separated using a separatory funnel to obtain a phenol-lithium solution. This solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0074] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.1:1:1, put solid lithium phenolate and lithium iron phosphate into a ball mill jar, with a ball-to-material ratio of 1:10, a ball milling speed of 350 r / min, and ball mill for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace to prepare for solid phase repair.
[0075] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0076] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 143 mAh / g. After 200 cycles, the battery capacity retention rate was 83.26%.
[0077] Example 3
[0078] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution (lithium to phenol molar ratio 1:1). The lithium hydroxide and phenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of lithium phenol solution was separated using a separatory funnel to obtain a lithium phenol solution. This lithium phenol solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0079] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.05:1:1, put solid lithium phenolate and lithium iron phosphate into a ball mill jar, with a ball-to-material ratio of 1:10, a ball milling speed of 350 r / min, and ball mill for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace to prepare for solid phase repair.
[0080] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0081] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 145 mAh / g, and after 200 cycles, the battery capacity retention rate was 85.14%.
[0082] Example 4
[0083] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution. The molar ratio of lithium to phenol was 1:1.05. The lithium hydroxide and phenol organic solvent were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of lithium phenol solution was separated using a separatory funnel to obtain a lithium phenol solution. The lithium phenol solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0084] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and load solid lithium phenolate and lithium iron phosphate into a ball mill jar according to the element molar ratio: Li:Fe:P=1:1:1, with a ball-to-material ratio of 1:10, a ball milling speed of 350r / min, and ball milling for 2h. After ball milling is completed, place the mixed powder in an atmosphere furnace for solid phase repair.
[0085] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0086] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 139 mAh / g. After 200 cycles, the battery capacity retention rate was 85.46%.
[0087] Example 5
[0088] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution. The molar ratio of lithium to phenol was 1:1.1. The lithium hydroxide and phenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of phenol-lithium solution was separated using a separatory funnel to obtain a phenol-lithium solution. This solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0089] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and load solid lithium phenolate and lithium iron phosphate into a ball mill jar according to the element molar ratio: Li:Fe:P = 1.2:1:1, with a ball-to-material ratio of 1:10. The ball milling speed is 350r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace to prepare for solid phase repair.
[0090] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0091] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 132 mAh / g. After 200 cycles, the battery capacity retention rate was 88.45%.
[0092] Example 6
[0093] Ethanol reagent and phenol powder were added to a beaker. The phenol dissolved in the ethanol reagent to form a phenol organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution (lithium to phenol molar ratio 1:1.03). The lithium hydroxide and phenol organic solvent were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of lithium phenol solution was separated using a separatory funnel to obtain a lithium phenol solution. This lithium phenol solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium phenol.
[0094] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.02:1:1, put solid lithium phenolate and lithium iron phosphate into a ball mill jar, with a ball-to-material ratio of 1:10, a ball milling speed of 400 r / min, and ball mill for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace to prepare for solid phase repair.
[0095] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 300°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 600°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature to obtain the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0096] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 137 mAh / g, and after 200 cycles, the battery capacity retention rate was 78.36%.
[0097] Example 7
[0098] Ethanol reagent and benzoic acid powder were added to a beaker. The benzoic acid dissolved in the ethanol reagent to form an organic solvent with a mass concentration of 30%. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of a 0.5 M lithium hydroxide aqueous solution (lithium to benzoic acid molar ratio of 1:1.2). The lithium hydroxide and benzoic acid organic solvent were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of lithium benzoate solution was separated using a separatory funnel to obtain a lithium benzoate solution. The lithium benzoate solution was then evaporated and crystallized in a rotary evaporator to obtain solid lithium benzoate.
[0099] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.01:1:1, put lithium benzoate solid and lithium iron phosphate into a ball mill jar, the ball-to-material ratio is 1:10, the ball milling speed is 350 r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace, ready for solid phase repair.
[0100] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0101] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 147 mAh / g, and after 200 cycles, the battery capacity retention rate was 88.36%.
[0102] Example 8
[0103] Ethanol reagent and p-phenol powder were added to a beaker. The p-phenol dissolved in the ethanol reagent to form a 30% p-phenol organic solvent. A 0.5 mol / L lithium hydroxide solution was prepared by adding 1 L of 0.5 M lithium hydroxide aqueous solution (lithium to p-phenol molar ratio 1:1.2). The lithium hydroxide and p-phenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of p-phenol lithium solution was separated using a separatory funnel to obtain a p-phenol lithium solution. This p-phenol lithium solution was then evaporated and crystallized in a rotary evaporator to obtain solid p-phenol lithium.
[0104] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.01:1:1, put lithium phenolate solid and lithium iron phosphate into a ball mill jar, the ball-to-material ratio is 1:10, the ball milling speed is 350 r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace, ready for solid phase repair.
[0105] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0106] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 143 mAh / g, and after 200 cycles, the battery capacity retention rate was 89.64%.
[0107] Example 9
[0108] Ethanol reagent and 2-ethylphenol powder were added to a beaker. The 2-ethylphenol dissolved in the ethanol reagent to form a 30% organic solvent. A 0.5 mol / L lithium hydroxide solution was prepared. 1 L of a 0.5 M lithium hydroxide aqueous solution was taken, with a lithium to 2-ethylphenol molar ratio of 1:1.2. The lithium hydroxide and 2-ethylphenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of 2-ethylphenol lithium solution was separated using a separatory funnel to obtain a 2-ethylphenol lithium solution. This 2-ethylphenol lithium solution was then evaporated and crystallized in a rotary evaporator to obtain solid 2-ethylphenol lithium.
[0109] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.01:1:1, put 2-ethylphenol lithium solid and lithium iron phosphate into a ball mill jar, the ball-to-material ratio is 1:10, the ball milling speed is 350 r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace, ready for solid phase repair.
[0110] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0111] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 145 mAh / g, and after 200 cycles, the battery capacity retention rate was 91.24%.
[0112] Example 10
[0113] Ethanol reagent and 3-ethylphenol powder were added to a beaker. The 3-ethylphenol dissolved in the ethanol reagent to form a 30% ethylphenol organic solvent. A 0.5 mol / L lithium hydroxide solution was prepared. 1 L of a 0.5 M lithium hydroxide aqueous solution was taken, with a lithium to 3-ethylphenol molar ratio of 1:1.2. The lithium hydroxide and 3-ethylphenol organic solvents were mixed and stirred continuously for 45 min. After the reaction was complete, the mixture was allowed to stand for 1 h, resulting in layering. The lower layer of 3-ethylphenol lithium solution was separated using a separatory funnel to obtain a 3-ethylphenol lithium solution. The 3-ethylphenol lithium solution was then evaporated and crystallized in a rotary evaporator to obtain solid 3-ethylphenol lithium.
[0114] Take 50g of lithium iron phosphate powder to be repaired, test the element content in lithium iron phosphate, and according to the element molar ratio: Li:Fe:P = 1.01:1:1, put 3-ethylphenol lithium solid and lithium iron phosphate into a ball mill jar, the ball-to-material ratio is 1:10, the ball milling speed is 350 r / min, and the ball milling is carried out for 2 hours. After the ball milling is completed, place the mixed powder in an atmosphere furnace, ready for solid phase repair.
[0115] The ball-milled material was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 375°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 675°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature, yielding the repaired lithium iron phosphate cathode material. A protective atmosphere was used throughout the solid-phase repair process.
[0116] The repaired lithium iron phosphate cathode material was used to prepare a lithium iron phosphate battery. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 139 mAh / g, and after 200 cycles, the battery capacity retention rate was 92.41%.
[0117] Comparative Example 1
[0118] Waste lithium iron phosphate powder (the lithium iron phosphate powder to be repaired in Examples 1-8) was used to prepare coin cells. The electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 101 mAh / g and the number of cycles was only 78.
[0119] Comparative Example 2
[0120] The decommissioned lithium iron phosphate powder (the lithium iron phosphate powder to be repaired in Examples 1-8) was placed in an atmosphere furnace, and hydrogen was introduced at a flow rate of 0.5 L / min. The temperature was increased from room temperature to 300°C at a rate of 5°C / min, and held for 2 hours. The temperature was then increased to 600°C at a rate of 5°C / min, and held for 8 hours. After the holding period, the material was allowed to cool naturally to room temperature to obtain the repaired lithium iron phosphate cathode material. A protective atmosphere was introduced throughout the solid-phase repair process.
[0121] The sintered lithium iron phosphate powder was used to prepare coin cells, and the electrochemical performance was tested. Under 0.2C charge-discharge cycling, the battery capacity was 120mAh / g, and the number of cycles was only 124.
Claims
1. The application of organic lithium salts in the repair of cathode materials for lithium-ion batteries, characterized in that, The organolithium salt is formed by the compound of formula (I) and an alkaline lithium salt; Equation (I); Wherein, R1 is OH or COOH; R2 is H or a C1~C5 alkyl group; The cathode material of the lithium-ion battery is lithium iron phosphate cathode material.
2. The application according to claim 1, characterized in that, The compound of formula (I) is selected from one or more of phenol, benzoic acid, p-phenylethylphenol, 2-ethylphenol and 3-ethylphenol; The alkaline lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, and lithium bicarbonate.
3. The application according to claim 1, characterized in that, The organic lithium salt is prepared according to the following steps: S) The compound shown in formula (I) is mixed with an aqueous solution of an alkaline lithium salt in an organic solvent, stirred and allowed to stand, the lower layer solution is separated, and the solvent is removed to obtain the organic lithium salt.
4. The application according to claim 3, characterized in that, Step S) specifically includes: S1) Mix the compound shown in formula (I) with an organic solvent to obtain an organic solution of the compound shown in formula (I); Alkaline lithium salt is mixed with water to obtain an aqueous solution of alkaline lithium salt; S2) Mix the organic solution of the compound shown in formula (I) with an alkaline lithium salt aqueous solution, stir and react, let stand, separate the lower layer solution, remove the solvent, and obtain the organic lithium salt; The mass concentration of the compound represented by formula (I) in the organic solution is 10% to 50%; The concentration of alkaline lithium salt in the alkaline lithium salt aqueous solution is 0.1~2 mol / L.
5. The application according to claim 3, characterized in that, The organic solvent is selected from one or more of ethanol, methanol, ethylene glycol and diethyl ether; the stirring reaction time is 0.5-3 h; the standing time is 0.5-2 h.
6. A method for targeted reduction and repair of lithium-ion battery cathode materials, characterized in that, Includes the following steps: A1) Mix the organic lithium salt with the positive electrode material of the lithium-ion battery to be repaired to obtain a mixed material; A2) The mixed material is first subjected to low-temperature pretreatment in a protective atmosphere, and then solid-state sintering is performed to obtain the repaired lithium-ion battery cathode material. The organolithium salt is formed by the compound of formula (I) and an alkaline lithium salt; Equation (I); Wherein, R1 is OH or COOH; R2 is H or a C1~C5 alkyl group; The cathode material of the lithium-ion battery to be repaired is lithium iron phosphate cathode material.
7. The method according to claim 6, characterized in that, In step A1), the organic lithium salt and the positive electrode material of the lithium-ion battery to be repaired are mixed in a molar ratio of Li, Fe and P (1~1.2):1:
1.
8. The method according to claim 6, characterized in that, The mixing method in step A1) is ball milling; the ball-to-material ratio in the ball milling is 1:(5~15); the rotation speed of the ball milling is 300~500 r / min; and the ball milling time is 0.5~8 h.
9. The method according to claim 6, characterized in that, The heating rate of the low-temperature pretreatment is 1~10℃ / min; the temperature of the low-temperature pretreatment is 100℃~400℃; and the holding time of the low-temperature pretreatment is 1~8 h. The heating rate of the solid-state sintering is 1~10℃ / min; the solid-state sintering temperature is 400℃~1000℃; and the holding time of the solid-state sintering is 3~12 h.
10. The method according to claim 9, characterized in that, The flow rate of the protective atmosphere is 0.1~3 L / min; the protective atmosphere is selected from one or more of hydrogen, argon and nitrogen. The heating rate of the low-temperature pretreatment is 3~6℃ / min; the temperature of the low-temperature pretreatment is 350℃~390℃; and the holding time of the low-temperature pretreatment is 1~3 h. The heating rate of the solid-state sintering is 3~6℃ / min; the solid-state sintering temperature is 600℃~700℃; and the holding time of the solid-state sintering is 6~10 h.
Citation Information
Patent Citations
Method for regenerating positive active material from waste lithium iron phosphate batteries
CN106910889A
Green remediation regeneration technology of lithium iron phosphate material in waste battery
CN106976852A
Recycling treatment method of waste and old lithium iron phosphate battery anode materials
CN102208706A
Treatment process for regenerating lithium iron phosphate from waste lithium iron phosphate batteries
CN113788468A